Forex conquered : high probability systems and strategies for active traders - Person, John L. (Hoboken, N.J. : J. Wiley & Son, 2007)
Covers from trading systems to money management to emotions, he explains easily how to pull money consistently from the most complicated financial market in the world. John packs more new, innovative information into this book than ever seen in a trading book before.
Includes index.
oif 31/07/15
Loans
Keywords: Foreign exchange market; Foreign exchange futures; Stocks; Investment analysis